Signalling waiting times to citizens on public oral healthcare providers' websites - Söderlund Riitta (Taylor & Francis, 2025)
Objective: The study aimed to analyse the usefulness of signalling waiting times to citizens on the websites of public primary oral healthcare providers in Finland. Finnish laws require this signalling.
Material and methods: We gathered data with two cross-sectional surveys in 2021. One electronic questionnaire was for Finnish-speaking citizens in Southwest Finland. The other was for public primary oral healthcare managers (n = 159). We also gathered data on 15 public primary oral healthcare providers’ websites. For the theoretical framework, we combined the agency and signalling theories.
Results: Of the citizen respondents (n = 411), 57% knew about the waiting time signalling on the websites. The respondents considered waiting time a high-priority criterion in choosing a dentist, but they rarely searched for information anywhere on the choice of a dentist, wanting to visit the dentist they had earlier visited. The quality of signalled waiting times was low. One out of five managers (response rate 62%) answered that signalled waiting times were based on speculation.
Conclusions: Waiting times were signalled to comply with the legislation rather than to inform citizens and to reduce information asymmetry. Further research is needed to acquire information on rethinking waiting time signalling and its desired goals.